Sustainable seaweed aquaculture and climate change in the North Atlantic: challenges and opportunities - Veenhof, Reina J.; Burrows, Michael T.; Hughes, Adam D.; Michalek, Kati; Ross, Michael E.; Thomson, Alex I.; Fedenko, Jeffrey; Stanley, Michele S. (Frontiers in Marine Science, 2024)
Seaweed aquaculture is gaining traction globally as a solution to many climate issues. However, seaweeds themselves are also under threat of anthropogenically driven climate change. Here, we summarize climate-related challenges to the seaweed aquaculture industry, with a focus on the developing trade in the North Atlantic. Specifically, we summarize three main challenges: i) abiotic change; ii) extreme events; and iii) disease & herbivory. Abiotic change includes negative effects of ocean warming and acidification, as well as altered seasonality due to ocean warming. This can lower biomass yield and change biochemical composition of the seaweeds. Extreme events can cause considerable damage and loss to seaweed farms, particularly due to marine heatwaves, storms and freshwater inputs. Seaweed diseases have a higher chance of proliferating under environmentally stressful conditions such as ocean warming and decreased salinity. Herbivory causes loss of biomass but is not well researched in relation to seaweed aquaculture in the North Atlantic. Despite challenges, opportunities exist to improve resilience to climate change, summarized in three sections: i) future proof site selection; ii) advances in breeding and microbiome manipulation; and iii) restorative aquaculture. We present a case study where we use predictive modelling to illustrate suitable habitat for seaweed cultivation in the North Atlantic under future ocean warming. Notably, there was a large loss of suitable habitat for cultivating Alaria esculenta and Laminaria digitata. We show how selection and priming and microbe inoculates may be a cost-effective and scalable solution to improve disease- and thermal tolerance. Co-cultivation of seaweeds may increase both yield and biodiversity co-benefits. Finally, we show that aquaculture and restoration can benefit from collaborating on nursery techniques and push for improved legislation.